Perceptions of Environmental Change and Climate Concern Among Idaho's Farmers. Issue 6 (3rd June 2017) - Running, Katrina; Burke, Jordan; Shipley, Kathleen
ABSTRACT: Climate change public opinion research has identified conservative political ideology as the primary predictor of skepticism about climate change's anthropogenic causes. Most farmers in Idaho are politically conservative, but they are also a unique group for whom observing their environment is part of daily life and work. We use data from in-depth interviews with 30 Idaho farmers to examine the relationship between observations of specific environmental changes and climate concern. We find that while most farmers report noticing changes in precipitation patterns, growing season length, and winter temperatures, few farmers connect these with long-term global climate change. These findings have two important implications: 1) direct experience, even in the form of disruption to an individual's economic security, is not enough to overcome the influence of political ideology on climate change beliefs, and 2) acknowledging climate variation is not sufficient to convince individuals that the changes are produced by human activities.